2013
DOI: 10.1111/bju.12286
|View full text |Cite
|
Sign up to set email alerts
|

Impact of laparoscopic sacrocolpopexy on symptoms, health‐related quality of life and sexuality: a medium‐term analysis

Abstract: Objective• To evaluate the impact of laparoscopic sacrocolpopexy on symptoms, health-related quality of life (HRQL) and sexuality among women with symptomatic urogenital prolapse (UGP). Patients and Methods• A prospective analysis was carried out including 148 women with symptomatic UGP.• Baseline characteristics, medical and obstetric history were recorded.• The Pelvic Organ Prolapse Quantification (POP-Q) classification was used to stage the UGP. Validated tools were used to evaluate symptoms (Pelvic Floor D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 43 publications
(46 reference statements)
3
6
0
Order By: Relevance
“…Improvement regarding sexual activity was significant at 6 and 12 months postoperatively. As the excellent functional results and quality-of-life of LSC for POP have been reported widely (8,11,12), and there were no significant differences between the 2 groups in these areas in our study, the improvement in functional results and quality of life at 12 months were effectively supported. Okcu et al (13) identified no significant difference among The data were recorded as mean ± SD.…”
Section: Discussionsupporting
confidence: 63%
“…Improvement regarding sexual activity was significant at 6 and 12 months postoperatively. As the excellent functional results and quality-of-life of LSC for POP have been reported widely (8,11,12), and there were no significant differences between the 2 groups in these areas in our study, the improvement in functional results and quality of life at 12 months were effectively supported. Okcu et al (13) identified no significant difference among The data were recorded as mean ± SD.…”
Section: Discussionsupporting
confidence: 63%
“…The postoperative Urinary Distress Inventory-6 total score was similar to those in other studies. 13,22,23 The reoperation rate was 2.37%, which was similar to other studies in the literature. [24][25][26][27] In all 5 cases, the pelvis was clear of adhesions with the added advantage of not having to remove an old mesh.…”
Section: Karon and Chatterjeesupporting
confidence: 87%
“…The PFDI-20 and PFIQ-7 scores ( Table 2) were comparable to the post-sacrocolpopexy and post-pelvic-surgery scores found in the literature. [13][14][15][16][17][18][19][20][21][22] Patients reported a feeling of overall improvement. The OAB symptom complaints comprised the most-common call-back reason for up to 3 months postoperatively and then steadily declined up to 1 year (Fig.…”
Section: Karon and Chatterjeementioning
confidence: 99%
“…The weak points of TVM remain vaginal scarring and sensory impairment caused by mesh implantation. It is worth emphasizing that the dyspareunia domain and total scores of FSFI improved significantly following LONG suspension, similar to the results of laparoscopic sacrocolpopexy 18 . The Taiwan translation of the FSFI has been validated for linguistic accuracy 19 .…”
Section: Discussionsupporting
confidence: 74%